"Save my kid" : how families of critically ill children cope, hope, and negotiate an unequal healthcare system - Gengler, Amanda M. (New York University Press, 2020)
A frank analysis of the medical and emotional inequalities that pervade the healthcare process for critically ill children Families who have a child with a life-threatening illness face a daunting road ahead of them, one that not only upends their everyday lives, but also strikes at the very heart of parenthood. In "Save My Kid," Amanda M. Gengler traces the emotional difficulties these families navigate as they confront a fundamentally unequal healthcare system in the United States. Gengler reveals the unrecognized, everyday inequalities tangled up in the process of seeking medical care, showing how different families manage their children's critical illnesses. She also uncovers the role that emotional goals--deeply rooted in the culture of illness and medicine--play in medical decision-making, healthcare interactions, and the end of children's lives. A deeply compassionate read, "Save My Kid" is an inside look at inequality in healthcare among those with the most at stake.